Learning Malay food & table manners through simulation : spicing up the traditional teaching method - Nurul Huda Razalli; Mohd ‘Adlan Mohd Shariffuddin (Penerbit Universiti Kebangsaan Malaysia, 2022)
The traditional way of teaching Malay food and table manners through only lecture classes restricts students' from truly appreciating the uniqueness of the Malays' eating culture, especially for non-natives. Thus, this innovation study was conducted to describe Malaysian health sciences students' experiences while participating in the simulation activity, as well as to learn about its usefulness in increasing student learning experiences. Following a classroom lecture on the topic of Malay Cuisine, a kenduri (feast) simulation involving ten traditional Malay table manners was conducted as part of in-class activity. An online survey was used to obtain feedback from 90 undergraduate students (Nutrition, n = 43, Dietetics, n = 19 and Optometry, n = 28), who enrolled in the course Multiethnic Cuisine & Etiquette as elective credits. Overall, students responded very positively to this learning activity. The results demonstrate that through peer-to-peer learning, this in-class simulation has enabled the majority of students to increase their knowledge (95.56%), understanding (97.78%), and interest (92.22%) in Malay food and table manners. This learning method has made both Malay (n = 56, 62%) and non-Malay (n = 34, 38%) students more appreciative of Malay culture. The findings show that in-class simulation is a useful and effective method for learning about Malay food and table manners resulting in a better learning experience.